Microfluidic Based Whole-Cell Biosensors for Simultaneously On-Site Monitoring of Multiple Environmental Contaminants - Cao, Yiqi; Zhang, Baiyu; Zhu, Zhiwen; Xin, Xiayin; Wu, Hongjing; Chen, Bing (Frontiers in Bioengineering and Biotechnology, 2021)
Monitoring of environmental contaminants serves a vital role in proactive environmental management and pollution control. Research efforts have been centered on the development of robust whole-cell biosensors in recent years. However, data acquisition, multiple contaminants detection and biosafety issues limit the on-site application of such biosensors. Microfluidic system exhibits great potential to face these challenges via coupling biosensors. Here, we prospect a novel microfluidic based whole-cell biosensor (MWCB) for multiplexing monitoring of diverse contaminants, and design strategies to further increase the specificity, sensitivity and accuracy, reduce signal delay and expand shelf life of the proposed MWCB for on-site environmental applications. The development of MWCB demands multidisciplinary cooperation, and the sensing platforms are highly promising for real-world contaminants monitoring.